2013
DOI: 10.1371/journal.pone.0072465
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Questionnaire to Detect Behavior Change in Multiple Advance Care Planning Behaviors

Abstract: IntroductionAdvance directives have traditionally been considered the gold standard for advance care planning. However, recent evidence suggests that advance care planning involves a series of multiple discrete behaviors for which people are in varying stages of behavior change. The goal of our study was to develop and validate a survey to measure the full advance care planning process.MethodsThe Advance Care Planning Engagement Survey assesses “Process Measures” of factors known from Behavior Change Theory to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(179 citation statements)
references
References 14 publications
0
172
2
2
Order By: Relevance
“…21 The group visits involve 2 sessions of 2 hours each, 1 month apart, co-facilitated by a geriatrician and a social worker. Table 1 provides an overview of the GMV structure, facilitator considerations, session format, and documentation and billing details.…”
Section: Conversation Group Medical Visitmentioning
confidence: 99%
“…21 The group visits involve 2 sessions of 2 hours each, 1 month apart, co-facilitated by a geriatrician and a social worker. Table 1 provides an overview of the GMV structure, facilitator considerations, session format, and documentation and billing details.…”
Section: Conversation Group Medical Visitmentioning
confidence: 99%
“…The surrogate needs to be asked to assume the responsibility and to agree to his or her role, and there needs to be communication and documentation of the surrogate as a medical power of attorney in the medical record. 26,28 In some cases, it may be appropriate for clinicians to facilitate a family meeting or conference call to assist patients in identifying and communicating their wishes with a surrogate and others they wish to be involved.…”
Section: Identifying Surrogate Decision Makersmentioning
confidence: 99%
“…Previous research showed that the behaviour change theory is important in motivating individuals to engage in ACP [9]. According to this theory, willingness to engage in ACP behaviour is determined by knowledge and beliefs about ACP and expectations about treatment outcomes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to this theory, willingness to engage in ACP behaviour is determined by knowledge and beliefs about ACP and expectations about treatment outcomes [9][10][11]. Increased public awareness of the importance of timely end-of-life discussions may facilitate patients' and loved ones' willingness to be engaged in end-of-life care discussions and may improve patient empowerment [12,13].…”
Section: Introductionmentioning
confidence: 99%